(3ahGFO GdbGVi CHh WGgQ eMeO Hf CMeO Hf YHO Gddg Hf fUQ Hf HLjQ GdPgdi aj GdMOjKs - (3GdOQGbWfj , CHh GdMSf,J (B385 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdMGaX CHh GdbGSe Ydj Hf GdMSf Hf gHI Gddg GdTGaYi aeQ GdfGS jYfi Ydjg acGf jeQ HfG GdQcHGf afSCdge eG dgPG GdCeQ eG ddfGS s
(3BNQgG (B:s
(3bGd SeYJ eMeO Hf jhSa GdbQeGfi jbhd SeYJ GdKhQi jbhd eG ef Yde CaVd ef WdH GdYde EPG UMJ GdfjI ai WdHg Je GdLRA GdKGef ef MOjK GdbGVi CHj WGgQ GdPgdi s
(3Ydjg SeGY SfI (B555(3g` Ydi UGMH GdSeGY GdCUdis
(3JHUQI GdYfhGf (B:s
(3EfJbGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B157s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs